2017
DOI: 10.1016/j.firesaf.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on backdraught: The dependence on temperature

Abstract: This paper presents the results of a series of reduced scale experiments to investigate the temperature conditions leading to backdraught in a fire compartment (0.8m x 0.4m x 0.4m), using solid polypropylene pellets as the fuel. The factors of primary interest are the pre-burn time, before the fire becomes oxygen limited, the duration of door closure, and the temperature distribution in the compartment. It is shown that the temperature inside the compartment is crucial for the occurrence of backdraught. Above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…It is observed that when CO/CO 2 was above 0.35, backdraft occurs, lower than this value, the spark can only ignite the unburned smoke and re-ignite the fuel tray only, with no obvious fireball indicating backdraft. It should be noted that even with an extremely long time of door closure with lower temperature about 200°C, a re-ignition is still possible, for details see [20]. It should also be noted that there were only three instances of backdraft observed in this series of eight piloted ignition tests, so it is hard to define the boundary between backdraft and non-backdraft events with any confidence.…”
Section: Gas Concentrationsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is observed that when CO/CO 2 was above 0.35, backdraft occurs, lower than this value, the spark can only ignite the unburned smoke and re-ignite the fuel tray only, with no obvious fireball indicating backdraft. It should be noted that even with an extremely long time of door closure with lower temperature about 200°C, a re-ignition is still possible, for details see [20]. It should also be noted that there were only three instances of backdraft observed in this series of eight piloted ignition tests, so it is hard to define the boundary between backdraft and non-backdraft events with any confidence.…”
Section: Gas Concentrationsmentioning
confidence: 91%
“…The conditions for backdraft can be achieved after a fire has become well established, but it has already been demonstrated that fire growth to flashover is not required [20]. Flashover, when it occurred, was identified during these tests by a rapid increase in burning rate, a significant increase in temperature, and external plume burning.…”
Section: Methodsmentioning
confidence: 99%
“…Наиме, током пожара у затвореном простору мо же се постићи фаза у којој топлотно зрачење пламена, врући га совити продукти сагоревања и загрејане површине кон стру к тив них елемената грађевинске конструкције објекта проузрокују пи ролизу свих присутних горивих материјала и њихово паљење. Овај изненадни и нагли прелаз пожара из фазе развоја у потпуно развијену фазу назива се флешовер (flashover) (Wu, Carvel, 2017). За разлику од флешовера, који подразумева пламени удар венти ли саног простора, у одређеним условима ограничена вентилација може резултирати још значајнијом концентрацијом смеше проду ка та непотпуног сагоревања и несагорелих продуката пиролизе.…”
Section: уводunclassified
“…According to the experimental results, they established a theoretical model and deduced the critical condition of backdraft. Wu et al [ 26 , 27 ] conducted reduced-scale experiments to study temperature conditions and critical factors of backdraft. Their results indicated that before the opening of a compartment, maximum temperature and the CO/CO2 ratio in the compartment were crucial factors that determined whether backdraft occurred or not.…”
Section: Introductionmentioning
confidence: 99%